Nephro and neurotoxicity of calcineurin inhibitors and mechanisms of rejections: A review on tacrolimus and cyclosporin in organ transplantation - Zahra Tolou-Ghamari (Society of Diabetic Nephropathy Prevention, 2012)
Context: In the meadow of medical sciences substituting a diseased organ with a healthy one from another individual, dead or alive, to allow a human to stay alive could be consider as the most string event. In this article we review the history of transplantation, mechanisms of rejection, nephro-neurotoxicity of tacrolimus and cyclosporin in organ transplantations. Evidence Acquisitions: Directory of Open Access Journals (DOAJ), Google Scholar, Pubmed (NLM), LISTA (EBSCO) and Web of Science have been searched. Results: The first reference to the concept of organ transplantation and replacement for therapeutic purposes appears to be to Hua-To (136 to 208 A.D), who replaced diseased organs with healthy ones in patients under analgesia induced with a mixture of Indian hemp. In 1936, the first human renal transplant performed by Voronoy in Russia. The first liver transplant in humans was performed on March 1, 1963 by Starzl in Denver, USA. Medawar was the first to assert that rejection was an immunological response, with the inflammatory reaction due to lymphocyte infiltration. Consequently, rational immunosuppressive therapies could inhibit deleterious T-cell responses in an antigen specific manner. Conclusions: Searching related to the history of organ transplantation from mythic to modern times suggests that, to prevent graft rejection, minimize nephro and neuro toxicity monitoring of immunosupressive concentrations could provide an invaluable and essential aid in adjusting dosage to ensure adequate immunosuppression.